[Delivery of sugar cane to Brechin Castle sugar factory] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Lorries lined up for weighing of sugar cane at the Brechin Castle sugar factory.
Cataloger's title
Keywords: Sugarcane -- Trinidad and Tobago